The rapid rise of agricultural mechanization in Myanmar. (May 2021) - Belton, Ben; Win, Myat Thida; Zhang, Xiaobo; Filipski, Mateusz
Highlights: Myanmar has experienced extremely rapid agricultural mechanization since 2011. Agricultural machinery is close to scale-neutral at point of use. Small farm sizes do not hinder uptake due to availability of outsourcing services. Demand for machines is driven by labor scarcity, timeliness, risk, drudgery aversion. Supply of machine outsourcing services facilitated by reforms to trade, banking, land tenure. Abstract: The past decade has seen a resurgence of interest in the role of mechanization in agricultural development. This literature has given rise to debates over the design of institutions and policies to facilitate accelerated mechanization, the role of outsourcing services in overcoming problems of access to machinery, and questions regarding the future of smallholder agriculture. We contribute to these debates using two pairs of complementary demand side (farm household) and supply side (agricultural machinery retailer) surveys, implemented in Myanmar in 2016 and 2017 across two major agro-ecological zones. Our analysis provides evidence that extremely rapid agricultural mechanization took place during the period of political and economic reforms from 2011 to 2020. In both zones surveyed, use of machinery for land preparation, harvesting, and threshing was close to scale-neutral due to a dynamic outsourcing services market. Rather than representing a single transformational change, mechanization's broad appeal to farm households results from an accumulation of incremental, overlapping, complementary advantages. These include labor savings, reduced drudgery, convenience, increased speed and timeliness of operations, improved ability to manage weather-related risks, and reduced loss of grain during harvesting. We provide examples of policies on trade, finance, and land tenure that contributed to this transformation with practical implications for ongoing policy debates on mechanization in other countries, and suggest some generalizable lessons.